Effect of audiovisual distraction on pediatric dental anxiety: A cross-sectional study - Padmanabhan, Vivek; Raidullah, Najma; Kamel, Balsam (Dental Journal (Majalah Kedokteran Gigi), 2024)
Background: Children's oral health and clinical management are significantly affected by dental fear and anxiety. Purpose: This study investigates the effectiveness of audiovisual distraction in reducing the anxiety levels of children visiting for dental treatment. Methods: Sixty pediatric patients ages 6–10 years were included in this cross-sectional study. They were divided into two groups”a study group and a control group”of 30 patients each. The study group was provided with a tablet and headphones that played their favorite shows, and the control group was not provided with any gadgets. For both groups, anxiety levels were scored using the Facial Image Scale. A two-way repeated-measure ANOVA test was used to compare the levels of dental anxiety among the study and control groups at three intervals: before treatment, during treatment, and after treatment. For the tests, the statistically significant difference was assumed at a p â‰¤ 0.05. Results: The children of both study and control groups had the same anxiety levels (p > 0.05) before the treatment. The study group had reduced anxiety levels compared to the children in the control group during and after the treatment, with p < 0.05. Conclusion: A child's favorite show can be played using a tablet and headphones for the child, as it has been shown to be an effective and easy method to reduce anxiety in children visiting dentists for operative procedures. This technique of distraction also reduces post-operative stress on the pediatric dentist.